REVOLUTIONIZING LIGHT INDUSTRY: THE DEVELOPMENT OF INNOVATIVE KNITWEAR PRODUCTS (Journal of Science-Innovative Research in Uzbekistan, 2023)
The light industry has witnessed a significant transformation in the development of innovative knitwear products. This article explores the changing landscape within the industry, highlighting the key factors contributing to this evolution. It aims to shed light on the impact of innovation on knitwear products, emphasizing the benefits and future prospects of these advancements